1990
DOI: 10.1126/science.1702902
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative Regulation of the Mouse α-Fetoprotein Gene in Adult Liver

Abstract: Transcription of the mouse alpha-fetoprotein gene is activated in the developing fetal liver and gut and repressed in both tissues shortly after birth. With germline transformation in mice, a cis-acting element was identified upstream of the transcription initiation site of the alpha-fetoprotein gene that was responsible for repression of the gene in adult liver. This negative element acts as a repressor in a position-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
94
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 24 publications
2
94
0
Order By: Relevance
“…[13][14][15][16][17] The AFP gene silencer elements existing between its enhancer and promoter regions play a major role in repressing the AFP gene expression in the low AFP-producing hepatoma cells. 18,19 In addition, McVey et at 10 have recently shown that only a G-to-A substitution at nucleotide −119 in the human AFP promoter is responsible for hereditary persistence of human AFP (HPAFP). In the present study, we constructed the retroviral vector in which the variant-type of the 0.3 kb human AFP promoter with a G-to-A substitution at nucleotide −119, a point mutation relevant to HPAFP, regulates the HSVtk gene expression (LNAFM0.3TK), and evaluated its efficacy in gene therapy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] The AFP gene silencer elements existing between its enhancer and promoter regions play a major role in repressing the AFP gene expression in the low AFP-producing hepatoma cells. 18,19 In addition, McVey et at 10 have recently shown that only a G-to-A substitution at nucleotide −119 in the human AFP promoter is responsible for hereditary persistence of human AFP (HPAFP). In the present study, we constructed the retroviral vector in which the variant-type of the 0.3 kb human AFP promoter with a G-to-A substitution at nucleotide −119, a point mutation relevant to HPAFP, regulates the HSVtk gene expression (LNAFM0.3TK), and evaluated its efficacy in gene therapy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The AFP gene has three characterized enhancers. These do not appear to be developmentally regulated, because they are strongly active in adult hepatocytes when combined with an active promoter (11)(12)(13).…”
mentioning
confidence: 99%
“…The albumin-positive AFP-negative adult hepatocyte phenotype is quite rare in cell lines from all species, except in those derived from the rat Reuber hepatoma. AFP repression is mediated by elements that extend from about Ϫ900 to Ϫ250 bp (12). In the mouse, an upstream part of this repressing region, the SBE/ p53RE (Ϫ878 to Ϫ762) binds p53, p73, and Smad4 (19,20).…”
mentioning
confidence: 99%
“…A point mutation (G to A) at Ϫ119 of AFP promoter is associated with naturally occurring Hereditary Persistence of AFP (HPAFP), which is predicted to improve HNF-1 binding and decrease NF-1 binding to the mutant sequence (12). The repressor region (Ϫ838 to Ϫ250) is required for AFP postnatal repression in pericentral hepatocytes but not essential for complete AFP repression in the intermediate zone and periportal hepatocytes (7,13). A site in the repressor region can be recognized by p53 family members, which leads to chromatin remodeling and AFP repression (14,15).…”
mentioning
confidence: 99%